Papers of Richard Whitington - Whitington, Richard; Australian Labor Party (1972)
Lists of the personal staff of the Prime Minister and Leader of the Opposition, 1975-1977; records of Federal Parliamentary Labor Party, 1972-1976; its "Rules and Standing Orders"; records of the Ministerial Offices, Queensland, 1974-1975.
Manuscript reference no. : MS 6478.
Personal staff member with the office of the Hon. E. G. Whitlam.
Keywords: Whitington, Richard -- Archives; Australia. -- Department of the Prime Minister and Cabinet -- Officials and employees -- Archives; Australian Labor Party -- Archives; Public officers -- Australia -- Archives; Australia -- Politics and government -- 1972-1975.; Public servants